Performance Analysis of the R290 Variable Geometry Gas Ejector Application for Other Refrigerants - Rafal Fingas; Guillaume Mass; Giorgio Besagni (Chemical Engineering Transactions, 2023)
Ejector refrigeration systems are promising alternative to standard vapour compression refrigeration systems. They can be driven with low-grade heat or solar systems, which make them even more renewable solution aligned with global energy transition. By implementing the controllable ejector, it can adapt to variable operating conditions, ensuring the high efficiency of both the device and the overall performance of the system. However, as it is fluid-driven device, its geometry has to be designed for particular fluid and typically requires redesigning when being applied for new applications. The R290 variable geometry gas ejector has been thoroughly tested for various spindle positions which ensured its highly efficient operation at different conditions. In this study, the same geometry was tested for other natural refrigerants of similar thermodynamic properties, i.e.R600a and R1270. The CFD analysis was based on a set of operating points for ejector-based air conditioning system working during the summer period with characteristic temperatures at evaporator and condenser. The controllable ejector was simulated for all the points with similar motive and suction nozzle parameters and the critical temperature at the outlet was determined. The analysis showed that the ejector can be used with other refrigerants maintaining high efficiency without any changes in geometry but for lower number of spindle positions. The obtained critical temperature indicates that with all the tested refrigerants the ejector-based cycle is able to work for cooling purposes during typical summer conditions for a wide range of temperatures.